2009
DOI: 10.1007/s11104-009-9939-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon dynamics following afforestation of a tropical savannah with Eucalyptus in Congo

Abstract: Soil organic matter is a key factor in the global carbon cycle, but the magnitude and the direction of the change in soil carbon after afforestation with Eucalyptus in the tropics is still a matter of controversy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…The magnitude and direction of changes in the soil C pool following reforestation can be highly variable and dependent on a variety of factors, including previous land use, species and soil properties (Epron et al, 2009). Meta-analysis have indicated a 10% reduction of soil C pools with land conversion from pasture to plantation (Guo and Gifford, 2002) and reductions in soil C between 6.7% and 15% across 153 sites with diverse plantation types (Berthrong et al, 2009).…”
Section: Planting For Carbon: An Ecosystem Approachmentioning
confidence: 99%
“…The magnitude and direction of changes in the soil C pool following reforestation can be highly variable and dependent on a variety of factors, including previous land use, species and soil properties (Epron et al, 2009). Meta-analysis have indicated a 10% reduction of soil C pools with land conversion from pasture to plantation (Guo and Gifford, 2002) and reductions in soil C between 6.7% and 15% across 153 sites with diverse plantation types (Berthrong et al, 2009).…”
Section: Planting For Carbon: An Ecosystem Approachmentioning
confidence: 99%
“…In addition, the fine particle fraction also plays an important role in the recovery of SOC stocks after land use change (Lima et al, 2006;Ouimet et al, 2007;Epron et al, 2009). Lima et al (2006) found little reduction in the preserved SOC and a significant increase in newly input C stocks in the clay and silt fractions in a ±33-year eucalyptus chronosequence (converted from pasture) in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate changes in SOC dynamics and stocks after a change in land use, the particle-size fractionation method for bulk soils has been employed (Zinn et al, 2002;Billings, 2006;Epron et al, 2009). In general, the sand fraction contains SOC that is relatively undecomposed and uncomplexed with mineral particles (Christensen, 2001) and which is assumed to be particulate organic matter (POM; Guggenberger et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…165 Only the carbon stock changes in the biomass are included in the calculation. The conversion 201 of cropland or grassland to plantations will likely increase or maintain unaltered the amount 202 of carbon in soils [16]. Therefore, it is conservatively assumed that the carbon stock changes 203 in the soil are equal to zero [11].…”
mentioning
confidence: 99%